From Trial to Chronic Epidural Electrical Stimulation: A Single-Patient Feasibility Study in Motor-Complete Spinal Cord Injury - Alena Militskova; Elvira Mukhametova; Artur Biktimirov; Vyacheslav Andrianov; Elena Yakovleva; Dinara Silantyeva; Igor Lavrov (Journal of Clinical Medicine, 2026)
Background/Objectives: Epidural electrical stimulation (EES) is a valuable intervention for motor recovery after spinal cord injury (SCI). However, evaluating expected outcomes can be challenging due to the difficulty of assessing residual functional connectivity and other key factors underlying the effects of EES. This case study investigates EES with two 8-contact percutaneous electrodes (Perc-EESs) as a prognostic tool and therapeutic bridge for chronic neuromodulation with EES in an individual with clinically motor-complete SCI. Methods: A 40-year-old male (AIS-B, Th5–Th6, >20 years since initial presentation followed by a complex history of progressive deterioration and two subsequent neurosurgical interventions) underwent a 7-day trial using Perc-EES, followed by chronic 5-6-5 Medtronic lead (Paddle-EES) implantation at the L2–S1 segments. Volitional motor control and EMG activity was assessed across three stages: Perc-EES at 5, 7, and 10 days post-enrollment; Paddle-EES at 13, 15, and 18 days post-enrollment; and at a 1-year follow-up (Paddle-EES (1y)). Evaluations were performed in side-lying and upright positions. Results: Without EES, no visible movements were observed. Perc-EES facilitated rhythmic EMG activity and initial voluntary movements, providing an early proof-of-concept that Perc-EES could serve as a preliminary assessment of the patient’s responsiveness to neuromodulation. Paddle-EES (1y) demonstrated a further improvement in motor coordination. Analysis using the Rudolph coefficient showed a distinct shift toward zero. This shift reflects stimulation-associated changes in EMG coordination, moving away from co-activation toward a more alternating activation pattern across side-lying and upright positions. Conclusions: This single-patient feasibility case study suggests that trial Perc-EES may have potential in determining the long-term benefits of chronic Paddle-EES in motor activation after SCI. While these conclusions remain preliminary, these findings can further serve as a potential diagnostic tool to optimize electrode placement and enhance overall recovery in motor-complete SCI patients.